1347. Omadacycline for Acute Bacterial Skin and Skin Structure Infections: Integrated Analysis of Randomized Clinical Trials. (26th November 2018) - Abrahamian, Fredrick M; Sakoulas, George; Tzanis, Evan; Manley, Amy; Steenbergen, Judith N; Das, Anita; Eckburg, Paul; McGovern, Paul
Abstract: Background: Skin infections are a significant medical burden for affected individuals and the healthcare system. The purpose of this investigation was to integrate the findings of two randomized studies of omadacycline (OMC) in ABSSSI. Methods: OMC in Acute Skin and Skin Structure Infections Study (OASIS)-1 initiated patients on intravenous (IV) OMC or linezolid (LZD) with a possible transition to oral formulation after at least 3 days of IV therapy. OASIS-2 investigated oral-only OMC. Treatment duration in both studies was 7–14 days. Early clinical response (ECR) in the mITT population, the primary endpoint in both studies, was defined as a ≥20% reduction in lesion size at 48–72 hours after treatment initiation. The secondary endpoint was investigator assessment of clinical response (IACR) at post-therapy evaluation (PTE) in the mITT and CE populations, 7–14 days after treatment initiation. Results: A total of 691 patients receiving OMC and 689 patients receiving LZD were included. The mean age of patients was 45 years, 64% were male, and 83% enrolled at US sites. Infection types: wound infections (46.8%), cellulitis/erysipelas (30.5%), major abscess (22.7%). Median lesion size was 316 cm 2 and 304 cm 2 in OMC and LZD patients, respectively . S. aureus was detected in 74.6% of patients, of which 43.4% had MRSA. 71% were mono-microbial Gram-positive infections, 15% were poly-microbial Gram-positive infections. OMC showed similar efficacy to LZD for the primary and secondary endpoints, as well as for mono-microbial and poly-microbial infections (figure). Clinical responses were similar across different infection types, lesion sizes, and baseline pathogens. Treatment-emergent adverse events (TEAEs), most mild or moderate, were reported by 51% and 41% of patients receiving OMC or LZD, respectively. Nausea and vomiting were more frequent for OMC patients in the OASIS-2 oral-only study while receiving the loading dose on Day 1 and 2. Serious AEs were reported by 2.3% and 1.9%, respectively. TEAEs leading to study drug discontinuation were reported by 1.7% and 1.5%, respectively. Conclusion: The integrated analysis of OASIS trials showed that oral and IV omadacycline was effective in the treatment of ABSSSI and was safe and generally well-tolerated by patients. Disclosures: F. M. Abrahamian, Allergan: Speaker's Bureau, Speaker honorarium. Melinta: Speaker's Bureau, Speaker honorarium. Merck: Speaker's Bureau, Speaker honorarium. Nabriva: Scientific Advisor, Consulting fee. Paratek: Scientific Advisor, Consulting fee. G. Sakoulas, Allergan: Consultant and Speaker, Consulting fee and Speaker honorarium. Sunovion Pharmaceuticals: Speaker, Speaker honorarium. The Medicines Company: Speaker, Speaker honorarium. Paratek Pharmaceuticals: Consultant, Consulting fee. Cidara Therapeutics: Scientific Advisor, Consulting fee. Arsanis Pharmaceuticals: Scientific Advisor, Consulting fee. E. Tzanis, Paratek Pharmaceuticals: Employee, Salary. A. Manley, Paratek Pharmaceuticals: Employee and Shareholder, Salary. J. N. Steenbergen, Paratek Pharmaceuticals: Employee and Shareholder, Salary. A. Das, Achaogen: Consultant, Consulting fee. Cempra: Consultant, Consulting fee. Contrafect: Consultant, Consulting fee. Nabriva: Consultant, Consulting fee. Paratek: Consultant, Consulting fee. Tetraphase: Consultant, Consulting fee. Theravance: Consultant, Consulting fee. Wockhardt: Consultant, Consulting fee. P. Eckburg, Paratek: Consultant, Consulting fee. P. McGovern, Paratek Pharmaceuticals: Employee, Salary.